Media exposure and adaptive coping in elite football - Kristiansen, E.; Roberts, G. C. (International Journal of Sport Psychology, 2011)
The purpose of this investigation was to examine how football players in a Premier Division in Europe experience media coverage (both outcome and negative content) during one season. We used sequential mixed methods in order to detect the different layers in this exploratory study. The results supported the hypothesis that a performance climate increases the perception of negative media exposure. Further, the football players coped with the media by using coping strategies such as social support, avoidance and problem-focused strategies. In addition, keeping the climate mastery oriented seemed pivotal, especially when a coach/team leader wanted to avoid negative media coverage to affect an entire team. Both individual coping strategies and team coping (mastery climate) seemed necessary to keep and protect a stable self-confidence among the football players and maintain team effort to perform.